The Effect of Short Stature on Children’s Cognitive Abilitiesand Psychosocial Condition - Heni Hastuti; Zahra Dzakiyatin Nisa; Husnia Auliyatul Umma; Anak Agung Alit Kirti Estuti Narendra Putri; Yusuf Ari Mashuri (Journal of Maternal and Child Health, 2020)
Background: Children are categorized as short stature when the Height for Age resultsare below the 3rd percentile of CDC growth chart standard. Short stature on children will have an impact on increased mortality and morbidity, children’s cognitive development,and psychological abilities. This study aims to investigate the effect of short stature on cognitive abilities and psychosocial condition of primary school children. Subjects and Method: A cross-sectional study was conducted at Pasar Kliwon 01 Primary School, Surakarta, Central Java, Indonesia. A total of 81 students from 3rd – 5th grades of were selected by consecutive sampling. The dependent variables were cognitive ability and psychosocial condition. The independent variable was body height. Body height was measured by microtoise. Cognitive ability was assessed based on mathematics, Indonesian language, and natural sciences score. Psychosocial condition was assessed using Pediatric Symptom Checklist-17. The data were analyzed by a multiple logistic regression. Results: Short stature increased cognitive ability (OR= 2.86; 95% CI= 1.03 to 7.92; p=0.043), and it was statistically significant. Short stature increased psychosocial condition, (OR= 2.24; 95% CI= 0.51 to 9.70; p= 0.279), but it was statistically non-significant. Conclusion: Short stature increases cognitive ability and psychosocial condition.